The Electrochemical Characteristics and Applicability of an Amorphous Sulfide-Based Solid Ion Conductor for the Next-Generation Solid-State Lithium Secondary Batteries - Aihara, Yuichi; Ito, Seitaro; Omoda, Ryo; Yamada, Takanobu; Fujiki, Satoshi; Watanabe, Taku; Park, Youngsin; Doo, Seokgwang (Frontiers in Energy Research, 2016)
Sulfide-based solid electrolytes (SEs) are of considerable practical interest for all solid-state batteries due to their high ionic conductivity and pliability at room temperature. In particular, iodine containing lithium thiophosphate is known to exhibit high ionic conductivity, but its applicability in solid-state battery remains to be examined. To demonstrate the possibility of the iodine-doped SE, LiI–Li3PS4, was used to construct two different types of test cells: Li/SE/S and Li/SE/LiNi0.80Co0.15Al0.05 cells. The SE, LiI–Li3PS4, showed a high ionic conductivity approximately 1.2 mS cm−1 at 25°C. Within 100 cycles, the capacity retention was better in the Li/SE/S cell, and no redox shuttle was observed due to physical blockage of SE layer. The capacity fade after 100 cycles in Li/SE/S cell was approximately 4% from the maximum capacity observed at 10th cycle. In contrast, the capacity fade was much larger in Li/SE/LiNi0.80Co0.15Al0.05 cell, probably due to the decomposition of the electrolyte at the operating potential range. Nevertheless, both the Li/SE/LiNi0.80Co0.15Al0.05 and Li/SE/S cells exhibited high coulombic efficiencies above 99.6 and 99.9% during charge–discharge cycle test, respectively. This indicates that a high energy density can be achieved without an excess lithium metal anode. In addition, it was particularly interesting that the SE showed a reversible capacity about 260 mAh g-SE−1 (the value calculated using the net solid electrolyte weight). This electrolyte may behave not only as an ionic conductor but also as a catholyte.